Clinical Characteristics of Gastrointestinal Malignancy and Validation of the IDIOM Model Among Patients With Iron Deficiency Anemia in Thailand - Kanjira Titsisaeng; Noraworn Jirattikanwong; Phichayut Phinyo; Pojsakorn Danpanichkul; Kanokwan Pinyopornpanish; Nithi Thinrungroj; Phuripong Kijdamrongthum; Apinya Leerapun; Taned Chitapanarux; Wasuwit Wanchaitanawong (JGH Open)
ABSTRACT Background Gastrointestinal malignancy is a concerning etiology of iron deficiency anemia (IDA). The IDIOM model predicts gastrointestinal malignancy risk in IDA patients using age, sex, hemoglobin, and mean corpuscular volume (MCV) as parameters. This study aimed to evaluate the clinical characteristics of gastrointestinal malignancy and externally validate the IDIOM model in Thai IDA patients. Methods A retrospective cross‐sectional study was conducted on adult IDA patients who underwent gastrointestinal endoscopy at Chiang Mai University Hospital between 2019 and 2023. Clinical characteristics were compared between patients with and without gastrointestinal malignancy. The IDIOM model's performance was assessed with discrimination, calibration, and clinical usefulness. To improve its performance, the model was updated using recalibration and refitting methods. Results Among 474 IDA patients, 101 (21.3%) had gastrointestinal malignancy, predominantly colorectal cancer (n = 80, 16.9%). Patients with gastrointestinal malignancy were more likely to be male (54.5% vs. 41.3%, p = 0.018), older (65.0 vs. 59.1 years, p < 0.001), symptomatic (78.2% vs. 44.0%, p < 0.001), and had higher rates of positive fecal immunochemical tests (80.9% vs. 29.5%, p < 0.001) and lower MCV (68.0 vs. 71.8 fl, p = 0.002). External validation of the IDIOM model yielded an AuROC of 62.9% (95% CI, 56.8%–68.9%). The calibration assessment revealed both underestimation and extreme risk predictions. After updating, the AuROC improved to 67.2% (95% CI, 61.1%–73.3%). Conclusion Distinct clinical features should alert physicians to the possibility of underlying gastrointestinal malignancy in IDA patients. Given the limited performance of the IDIOM model in the Thai population, a region‐specific prediction model tailored to local clinical characteristics is needed.